Epithelial stem cell culture: modeling human disease and applications for regenerative medicine. Issue 1 (December 2017) - Yamamoto, Yusuke; Ochiya, Takahiro
Abstract The inability to maintain the immaturity of stem cell populations in vitro restricts the long-term expansion of various types of human epithelial stem cells. However, recent technical advances in epithelial stem cell culture have led to the development of novel in vitro strategies for regenerating epithelial tissues and for closely mimicking human diseases such as cancer and inflammation. Specifically, improvements in culture conditions provided by small molecules in combination with three-dimensional (3D) culture approaches have facilitated the establishment of in vitro systems that recapitulate biological properties in epithelial organs, and these systems may be used to model disease. In this review article, we describe the biological significance of technical improvements in the development of these methods, focusing on human epithelial cells, including stratified and columnar epithelial cells. We also discuss the potential and future perspectives of this technology, which is only beginning to be explored.